2014
DOI: 10.3748/wjg.v20.i13.3418
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immune response during hepatitis C virus infection

Abstract: Hepatitis C virus (HCV) infection affects about 170 million people worldwide and it is a major cause of liver cirrhosis and hepatocellular carcinoma. HCV is a hepatotropic non-cytopathic virus able to persist in a great percentage of infected hosts due to its ability to escape from the immune control. Liver damage and disease progression during HCV infection are driven by both viral and host factors. Specifically, adaptive immune response carries out an essential task in controlling non-cytopathic viruses beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 107 publications
0
45
0
5
Order By: Relevance
“…However, the HCV-specific T cell immune response is critical for the control of HCV infection and HCV clearance (44,45). A case report indicated that HCV-specific CD4 + T cell responses are weak in chronic HCV infection (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, the HCV-specific T cell immune response is critical for the control of HCV infection and HCV clearance (44,45). A case report indicated that HCV-specific CD4 + T cell responses are weak in chronic HCV infection (46).…”
Section: Discussionmentioning
confidence: 99%
“…EBV produces a regulatory cytokine that is nearly indistinguishable from human IL-10 [36,37]. In response to attack by T cells, pathogens such as human immunodeficiency virus (HIV) and hepatitis C virus (HCV) have been demonstrated to avoid T-cell mediated response by the deletion of Teff epitopes [38][39][40].…”
Section: Tcr Degeneracy Epitope Redundancy Mimicry and Camouflagementioning
confidence: 99%
“…This process, known as "deimmunization" in the biologics industry, has been observed in the course of infection by RNA viruses (HIV, HCV [23][24][25] ). Evaluations of total T cell epitope content in bacterial genomes appear to confirm that deimmunization may also occur in selected bacteria.…”
Section: Defense Against Adaptive Immune Responsementioning
confidence: 99%